Security and Privacy Criteria to Evaluate Authentication Mechanisms in Proxy Mobile IPv6 (Jurnal Teknologi (Sciences & Engineering), 2015)
Mobility management protocols support mobility for roaming mobile nodes in order to provide seamless connectivity. Proxy Mobile IPv6 is a network-based localized mobility management protocol that is more suitable for resource constrained devices among different mobility management schemes. In this protocol, all mobility signaling procedures are completed by network entity not mobile node. According to the Proxy Mobile IPv6 architecture, an authentication procedure has a key role to protect the network against different security threats; however, the details of authentication procedure is not specified in this standard. In this paper, different security features are explored to evaluate the authentication protocols in Proxy Mobile IPv6. The existing authentication approaches can be analyzed based on these criteria to find security issues.